Teaching and Learning Hooke’s Law Using Physical, Interactive Software and Blended Approach: An Overview - Lee Sin Ang; Mohd Hafiz Yaakob; Siti Nurlia Ali; Zalina Zainal Abidin; Mohamad Hafiz Ismail; Nurul Ain Mohd Zaki (Universitas Negeri Semarang, 2025)
At present, with technological advancement and changes in students’ preferences, there are both challenges and opportunities to enhance the teaching and learning of subjects in science, technology, engineering, and mathematics (STEM). In this article, we explore reported works in established databases on the topic of Hooke’s Law, to see the approaches used in teaching and learning of the topic. Searches were performed in Web of Science, Scopus and Google Scholar databases, after which manual filtering for relevant articles was carried out by reading and browsing through the abstracts. Based on the types of works, the articles were separated into three parts: physical, interactive software, and blended. In total, 21 relevant articles were reviewed. The data obtained can be separated into three categories: physical, interactive software, and blended. Of the three, blended approaches were used the least. To further explore the topics discussed in the articles related to Hooke’s Law, a bibliometric study was performed. From the results, we found that, with the advantages offered by the blended approach, and none using artificial intelligence, there is still room for improvement to enhance the teaching of Hooke’s Law, specifically, and generally, on introductory physics subjects.